Dimensionamento da força de trabalho em organizações públicas: incorporando competências ao modelo - ROCHA, Thiago Almeida da (Universidade Federal do Pará, 2023)
This study aims to present a Workforce Dimensioning (WD) method that allows Brazilian public organizations to identify and integrate the professional profile based on competences into their WD processes. The research involved collecting data related to the work routine of 111 units of a public institution of the Brazilian judiciary system, such as productivity, quantity and duration. The results indicated the professional profile required by each of the 111 participating units and pointed out a deficit of 98 civil servants. Based on this, the applied methodology can indicate to the researched institution, in a technical way, how to raise and attract the appropriate number of personnel based on the profile of necessary servants. It is expected that this approach can help the studied organization to achieve a more efficient management of its workforce and, consequently, improve its personnel practices.